2007
DOI: 10.1111/j.1365-3024.2007.00999.x
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal immunization with Naegleria fowleri lysates and Cry1Ac induces metaplasia in the olfactory epithelium and increases IgA secretion

Abstract: According to previous reports, intranasal administration of the Cry1Ac protein alone or with amoebic lysates increases protection against Naegleria fowleri meningoencephalitis in mice, apparently by eliciting IgA responses in the nasal mucosa. In the current study, we performed an immunohistochemical analysis of IgA in the nasal mucosa of mice immunized intranasally with Cry1Ac, and amoebic lysates or a combination of both. The animals were sacrificed 24 h after the last immunization or after an intranasal let… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 42 publications
2
26
0
Order By: Relevance
“…In contrast, when Cry1Ac was co-administered intranasally as adjuvant with Naegleria fowleri lysates, only this treatment induced metaplasia in the olfactory epithelium and increased IgA secretion compared to immunization with lysates alone, effects that may be related to the increased protection conferred by this treatment; however, this result deserves further analysis ( Jarillo-Luna et al, 2008). Because when this protein is intranasally administered to mice, it is able to induce an increased proportion of activated T and B lymphocytes and an increased proportion of T lymphocytes producing cytokines and significant specific IgA and IgG antibody cell responses in nasal lymphocytes isolated from both nasal-associated lymphoid tissue (NALT) and nasal passages (NP) (Rodriguez-Monroy and Moreno-Fierros, 2010).…”
Section: Immune Responses Triggered By Bt Derivatesmentioning
confidence: 84%
“…In contrast, when Cry1Ac was co-administered intranasally as adjuvant with Naegleria fowleri lysates, only this treatment induced metaplasia in the olfactory epithelium and increased IgA secretion compared to immunization with lysates alone, effects that may be related to the increased protection conferred by this treatment; however, this result deserves further analysis ( Jarillo-Luna et al, 2008). Because when this protein is intranasally administered to mice, it is able to induce an increased proportion of activated T and B lymphocytes and an increased proportion of T lymphocytes producing cytokines and significant specific IgA and IgG antibody cell responses in nasal lymphocytes isolated from both nasal-associated lymphoid tissue (NALT) and nasal passages (NP) (Rodriguez-Monroy and Moreno-Fierros, 2010).…”
Section: Immune Responses Triggered By Bt Derivatesmentioning
confidence: 84%
“…In another study, it was determined that combined administration of Bacillus thuringiensis Cry1Ac protoxin and N. fowleri lysate provided the prolonged survival in mice compared to the mice only receiving N. fowleri lysate. Both mucosal IgG and IgA production enhanced, and the level of IgG remained high even after 2 months of inoculation and in the nasal lumen, IgA interaction with trophozoites was also reported on comparing to the non‐immunized animal where trophozoites penetrated into the nasal mucosa . Molecular based study revealed that Cry1Ac as an adjuvant administered along with amoebal lysate in STAT6+/+ mice has a 100% survival rate on comparison with STAT6−/− mice who did not survive on introducing intranasal N. fowleri .…”
Section: Managementmentioning
confidence: 84%
“…To date, we still do not know the precise mechanism by which neutrophils could be eliminating N. fowleri trophozoites. We have suggested that one of the main defence mechanism of the nasal mucosa against N. fowleri in previously immunized mice is the trophozoites phagocytosis by polymorphonuclear cells through their receptors at the Fc fraction of antibodies . However, there are many factors involved in neutrophil interaction with the microorganisms to avoid pathogen colonization.…”
Section: Discussionmentioning
confidence: 99%